Education of women entrepreneurs - Mateja Vadnjal; Jaka Vadnjal (Mednarodno Inovativno Poslovanje)
In this paper, we discuss the education of women entrepreneurs in different life stages. Education is one of the most widely used indicators of human capital. We assume that there are significant differences among women entrepreneurs at different stages of their lives, in the Early Career and Idealistic Achievement phase, Mid-Career or phase of Pragmatic Endurance, and thirdly, Advanced Career or Reinvention and Recontribution phase.